Differences between the recognition of known and unknown patterns - Šoliūnas , Alvydas; Gurčinienė , Ona (Psichologija, 2000)
Recognition of unknown meaningless figures was investigated in psychophysical experiment with the aim to clarify which stage of known figure recognition, facture extraction or extracted facture matching with the long-term memory representations, involves successive information processing. Five groups of test figures, consisting of four, five, six, seven, and eight horizontal and vertical line-segments, were composed. Each trial consisted of the following sequence: test figure for 10 ms; individually determined interstimulus interval; masking figure; delay of definite duration (8 values between 200 and 4700 ms); three figures for comparison. The task for subject was to find and indicate which one of three figures corresponds to the test figure. Recognition probability of unknown figures did not depend on the number of figure clements. This fact, together with the previously obtained reverse dependence of the recognition probability of known figures on their complexity, cd to the conclusion that the extraction of factures is the simultaneous process while the matching of extracted features with the long-term memory representations is the successive process. Retention of information in the short-term memory up to 5 s had no effect on the task performance.